2016
DOI: 10.1038/srep27445
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells induce platelet clearance in the liver via platelet desialylation in immune thrombocytopenia

Abstract: In addition to antiplatelet autoantibodies, CD8+ cytotoxic T lymphocytes (CTLs) play an important role in the increased platelet destruction in immune thrombocytopenia (ITP). Recent studies have highlighted that platelet desialylation leads to platelet clearance via hepatocyte asialoglycoprotein receptors (ASGPRs). Whether CD8+ T cells induce platelet desialylation in ITP remains unclear. Here, we investigated the cytotoxicity of CD8+ T cells towards platelets and platelet desialylation in ITP. We found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 52 publications
(96 reference statements)
1
57
0
Order By: Relevance
“…First, it is known that a proportion of patients initially diagnosed as ITP may have other, non-immune causes of thrombocytopenia 35 . Previous work by our group and others has indicated that treatment-refractory patients may not have any detectable anti-platelet antibodies in the first place 5,36 , and CD8-T cell mediated platelet clearance could be an alternative mechanism that maintains thrombocytopenia 37,38 .…”
Section: Discussionmentioning
confidence: 88%
“…First, it is known that a proportion of patients initially diagnosed as ITP may have other, non-immune causes of thrombocytopenia 35 . Previous work by our group and others has indicated that treatment-refractory patients may not have any detectable anti-platelet antibodies in the first place 5,36 , and CD8-T cell mediated platelet clearance could be an alternative mechanism that maintains thrombocytopenia 37,38 .…”
Section: Discussionmentioning
confidence: 88%
“…For example, only 60% to 70% of people are documented to have antibodies potentially indicating that non‐antibody‐dependent mechanisms are responsible for platelet destruction . When considering platelet destruction in humans with ITP who lack antibodies, CD8+ T cells result in direct platelet destruction and are also involved in subsequent platelet desialylation . It is unknown if these mechanisms occur in dogs …”
Section: Discussionmentioning
confidence: 99%
“…2,18 When considering platelet destruction in humans with ITP who lack antibodies, CD8+ T cells result in direct platelet destruction and are also involved in subsequent platelet desialylation. 2,18,[29][30][31][32] It is unknown if these mechanisms occur in dogs. 18 F I G U R E 3 The percentage of antiplatelet antibodies (APA) were recorded for dogs that were divided into 4 categories: infectious, neoplastic, other, and immune thrombocytopenia (ITP).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Several pathways have been postulated in the pathogenesis of ITP, including autoantibodies against platelet membrane GP complexes, 6 B-cell clonality, 7 T regulatory cell dysfunction 8 , and T lymphocyte-mediated cytotoxicity. 9 More recently, anti-GPIbα 10 and CD8 + T-cell mediated platelet desialylation 11 has been implicated in ITP. Herein, we describe a patient with primary ITP and acquired GT.…”
Section: Introductionmentioning
confidence: 99%